Mobiliser des traces du travail réel en formation : la photographie adressée - Filippi, Pierre-Alain; Félix, Marie-Christine; Mouton, Jean-Claude (Nouveaux cahiers de la recherche en éducation, 2022)
This article presents an educational method, “addressed photography,” that is backed by a theoretical framework located within a historical-cultural tradition. The method, developed based on real work documents—in this case the work of a student teacher—uses photography as a mediation tool in work-study programs, between the school (practicum) and the initial teacher-education institution (university courses). It focuses on student teachers’ development of experience, which it seeks to prompt and support through successive realizations in different stages, and by making use of educational contexts that vary with respect to both time and place.
Keywords: analyse du travail; análisis del trabajo; conciencia; conscience; desarrollo; development; développement; formación inicial de docentes; formation initiale des enseignants; fotografía; initial teacher education; photographie; photography; realization; work analysis